2016
DOI: 10.1016/j.visres.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The pattern ERG in chicks – Stimulus dependence and optic nerve section

Abstract: The chick is widely used in studies of eye growth regulation and myopia. The aim of this study was to explore the utility of pattern (p)ERG as a tool to assess retinal function in such studies. Effects of optical defocus and diffusing blur, manipulations used to alter eye growth experimentally, were evaluated. PERGs were recorded from White-Leghorn chickens, using a checkerboard pattern, including 8 spatial frequencies (0.05 to 2.2 c/d SF), 13 contrast levels (1–100%), and 8 temporal reversal frequencies (0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The remainder of the chick retina has an organization similar to that of humans with three layers of nuclei 35 . In terms of retinal electrophysiological responses, Ostrin et al showed that PERG responses were not affected despite the loss of retinal ganglion cells in chicks with optic nerve section (ONS), suggesting that retinal ganglion cells do not contribute to PERG in chicks 39 . These results await a systematic follow-up using pharmacological dissection to study the neuronal origins of MOFO responses.…”
Section: Discussionmentioning
confidence: 99%
“…The remainder of the chick retina has an organization similar to that of humans with three layers of nuclei 35 . In terms of retinal electrophysiological responses, Ostrin et al showed that PERG responses were not affected despite the loss of retinal ganglion cells in chicks with optic nerve section (ONS), suggesting that retinal ganglion cells do not contribute to PERG in chicks 39 . These results await a systematic follow-up using pharmacological dissection to study the neuronal origins of MOFO responses.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the PERG may also have some utility in estimating the visual acuity in the chicken. Using PERG, Ostrin et al (2016) estimated chick visual acuity to be approximately 2.2 cycles/degree, representing notably less than described by OKN testing methods (See Section 2.11). Ostrin et al (2016) speculate that that inherent differences in the visual pathways activated by PERG and OKN testing may be responsible for the difference estimation of visual acuity.…”
Section: Basic Anatomy and Physiologymentioning
confidence: 96%
“…Using PERG, Ostrin et al (2016) estimated chick visual acuity to be approximately 2.2 cycles/degree, representing notably less than described by OKN testing methods (See Section 2.11). Ostrin et al (2016) speculate that that inherent differences in the visual pathways activated by PERG and OKN testing may be responsible for the difference estimation of visual acuity. Schmid et al (2013) used multifocal ERG (mfERG) to study retinas of normal chicks and those with form-deprivation myopia.…”
Section: Basic Anatomy and Physiologymentioning
confidence: 96%
See 1 more Smart Citation
“…Attenuated pERGs to defocus (with plus lenses) and diffuse blur (Bangerter filters) have also been found in chicks. 8 Chin et al 9 have recently studied retinal responses to defocus blur as a function of the retinal region using global flash pattern multifocal ERGs (mfERG). They found a sign-dependent response to defocus in the pattern mfERGs, with the effect being stronger in near peripheral regions between approximately 9 degrees and 19 degrees eccentricity (mfERG rings 3 to 6).…”
mentioning
confidence: 99%